The silvering process in European eel (Anguilla anguilla) influences PAH metabolite concentration in bile fluid - consequences for monitoring - Nagel, Florian; Wagner, Carola; Hanel, Reinhold; Kammann, Ulrike (Chemosphere, 2012)
The stock of the catadromous European eel (Anguilla anguilla L.) continues to decline and there is growing evidence that poor health status due to contaminants might be a key element in this decrease. Organic contaminants such as polycyclic aromatic hydrocarbons (PAHs) belong to the major threats to yellow eel in their growth habitat and their metabolites are detectable in the bile. Starting the silvering process eels undergo physiological and morphological changes including cessation of feeding and downstream migration back to their spawning grounds. Reduced feed intake results in a diminishment of bile production and induces accumulation of e.g. PAH-metabolites in bile. Therefore, the aim of the present study was to demonstrate the impact of silvering on biliary PAH metabolite concentrations and to utilize normalization procedures to overcome silvering related accumulation effects of PAH-metabolites in eel bile. We investigated the hydroxyl-metabolites of pyrene (1-OH Pyr) and phenantrene (1-OH Phen) in the bile of different maturation stages of eels (silvering index I–V) from nine German rivers. We detected increasing absolute PAH metabolite levels in bile during the silvering process. The highest rise could be observed at the transition from pre migration stage III to the migrating stage IV, suggesting the onset of cessation of feeding at this stage. A cessation bias in PAH metabolite measurement could be diminished by normalization of absolute values against bile pigments (A 380, biliverdin). In conclusion, we demonstrated the impact of silvering on PAH metabolite concentrations in eel bile and present suitable normalization procedures to overcome silvering related accumulation effects. Thus, for a future eel monitoring we recommend (1) to regularly monitor PAH metabolites in bile, (2) to determine silvering index of eel and (3) to normalize PAH metabolite values in bile based on maturation/silvering stages. The knowledge of the silvering stage is mandatory for an unbiased evaluation of PAH contamination of ...